DEVELOPMENT OF MODERN URBAN ENVIRONMENT AS A FACTOR OF EXPANSION OF TOURIST GOALS - Tursunov Shavkat Sharibjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The urban environment is an important structural element of the city’s potential, due to which it directly fulfills its historical function as a source of development. A diverse and interconnected urban environment promotes the emergence and development of new ones in the most diverse areas of human activity. A comfortable urban environment for people directly ensures the physical, psychological and social well-being of the city’s inhabitants, and the harmonious, social and economic well-being of the city.